Creation, covenant, and the beginnings of Judaism : reconceiving historical time in the Second Temple period - Mermelstein, Ari. (Supplements to the Journal for the Study of Judaism, 2014)
This study examines the relationship between time and history in Second Temple literature. Numerous sources from that period express a belief that Jewish history began with an act of covenant formation and proceeded in linear fashion until the exile, an unprecedented event which severed the present from the past. The authors of Ben Sira, Jubilees , the Animal Apocalypse , and 4 Ezra responded to this theological challenge by claiming instead that Jewish history began at creation. Between creation and redemption, history unfolds as a series of static, repeating patterns that simultaneously account for the disappointments of the Second Temple period and confirm the eternal nature of the covenant. As iterations of timeless, cyclical patterns, the difficult post-exilic present and the glorious redemption of the future emerge as familiar, unremarkable, and inevitable historical developments.